Deciphering an Abnormal Layered‐Tunnel Heterostructure Induced by Chemical Substitution for the Sodium Oxide Cathode. Issue 4 (5th December 2019) - Xiao, Yao; Zhu, Yan‐Fang; Xiang, Wei; Wu, Zhen‐Guo; Li, Yong‐Chun; Lai, Jing; Li, Shi; Wang, Enhui; Yang, Zu‐Guang; Xu, Chun‐Liu; Zhong, Ben‐He; Guo, Xiao‐Dong
Abstract: Demands for large‐scale energy storage systems have driven the development of layered transition‐metal oxide cathodes for room‐temperature rechargeable sodium ion batteries (SIBs). Now, an abnormal layered‐tunnel heterostructure Na0.44 Co0.1 Mn0.9 O2 cathode material induced by chemical element substitution is reported. By virtue of beneficial synergistic effects, this layered‐tunnel electrode shows outstanding electrochemical performance in sodium half‐cell system and excellent compatibility with hard carbon anode in sodium full‐cell system. The underlying formation process, charge compensation mechanism, phase transition, and sodium‐ion storage electrochemistry are clearly articulated and confirmed through combined analyses of in situ high‐energy X‐ray diffraction and ex situ X‐ray absorption spectroscopy as well as operando X‐ray diffraction. This crystal structure engineering regulation strategy offers a future outlook into advanced cathode materials for SIBs. Abstract : An abnormal layered‐tunnel heterostructure Na0.44 Co0.1 Mn0.9 O2 cathode material induced by chemical element substitution is described. The crystal‐structure engineering strategy that was used gives an outlook into high‐performance sodium ion batteries.